The Benefit and Safety of Aspirin for Primary Prevention of Ischemic Stroke: A Meta-Analysis of Randomized Trials - Lei, Hong; Gao, Qian; Liu, Shan-Rong; Xu, Jian (Frontiers in Pharmacology, 2016)
Background: Although aspirin is effective in the secondary prevention of stroke among men and women, its use in primary prevention remains controversial. We conducted a meta-analysis of randomized trials to evaluate the benefit and safety of aspirin for the primary prevention of ischemic stroke. Methods: We searched 3 electronic databases (Medline, the Cochrane Central Register of Controlled Trials, and Embase) for articles published before August1st, 2016. Randomized trials reporting the effect of aspirin on the ischemic stroke and its side effects were included. We synthesized evidence qualitatively and useda fixed-effect model to quantify the effect of aspirin on the primary prevention of stroke when the heterogeneity was low, or else applied the random-effect model. Results: Fourteenrandomized trials were included. Overall, aspirin use was associated with a decreased risk of ischemic stroke compared with non-aspirin use (OR: 0.83, 95% CI: 0.74-0.93, P=0.45). In subgroup analyses, the effect of aspirin on ischemic stroke in apparently healthy adults remained significant (OR: 0.83, 95% confidence interval: 0.74-0.94, I2=22%, P=0.28 ;) while in patients with cardiovascular diseases there was no difference in the risk of ischemic stroke between aspirin and non-aspirin groups (OR: 0.75, 95% confidence interval: 0.44-1.29, P=0.46 ;). As for adverse effects, the prophylactic use of aspirin potentially increased the risk of serious bleeding events in a population of apparently healthy individuals and in patients with previous cardiovascular diseases. Conclusion: This meta-analysis of randomized trialsindicated that both the apparently healthy adults and patients with cardiovascular diseases will derive little protective benefit from aspirin considering the increased risk of severe bleeding events.